Effects of drying time on the formation of merged and soft MAPbI3 grains and their photovoltaic responses. Issue 8 (20th March 2023) - Chandel, Anjali; Ke, Qi Bin; Chiang, Shou-En; Cheng, Hsin-Ming; Chang, Sheng Hsiung
Abstract : The grain sizes of MAPbI3 films and the atomic contact strength at the MAPbI3 /P3CT-Na interface are manipulated by varying the drying time of saturated MAPbI3 precursor solutions, which influences the performance of the resultant perovskite photovoltaic cells. Abstract : The grain sizes of soft CH3 NH3 PbI3 (MAPbI3 ) thin films and the atomic contact strength at the MAPbI3 /P3CT-Na interface are manipulated by varying the drying time of the saturated MAPbI3 precursor solutions, which influences the device performance and lifespan of the resultant inverted perovskite photovoltaic cells. The atomic-force microscopy images, cross-sectional scanning electron microscopy images, photoluminescence spectra and absorbance spectra show that the increased short-circuit current density ( J SC ) and increased fill factor (FF) are mainly due to the formation of merged MAPbI3 grains. Besides, the open-circuit voltage ( V OC ) of the encapsulated photovoltaic cells largely increases from 1.01 V to 1.15 V, thereby increasing the power conversion efficiency from 17.89% to 19.55% after 30 days, which can be explained as due to the increased carrier density of the MAPbI3 crystalline thin film. It is noted that the use of the optimized drying time during the spin coating process results in the formation of merged MAPbI3 grains while keeping the contact quality at the MAPbI3 /P3CT-Na interface, which boosts the device performance and lifespan of the resultant perovskite photovoltaic cells.